2022
DOI: 10.1021/acssuschemeng.1c08602
|View full text |Cite
|
Sign up to set email alerts
|

Technoeconomic and Life-Cycle Assessment for Electrocatalytic Production of Furandicarboxylic Acid

Abstract: 2,5-Furandicarboxylic acid (FDCA) is a platform chemical for polyethylene furanoate (PEF) manufacturing, a promising biobased and green alternative to polyethylene terephthalate (PET) with a market size of 1.8 million tonne/ annum. There are several routes to produce FDCA, all through 5hydroxymethylfurfural (HMF) conversion. The traditional thermochemical process is highly energy intensive with a low yield. The electrocatalytic pathway, on the other hand, is gaining increased interest for it makes the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…By valorizing the biomass byproducts such as HMF via clean energy, a circular economy model can be established, which benefits both the biorefinery industry and the general public, rendering the electrochemical oxidation of HMF a highly researched topic. A recent techno-economic analysis demonstrates the considerable merits of electrochemical oxidation of HMF in both energy and material perspectives compared with conventional thermal catalysis ( Patel et al., 2022 ). Another profound benefit of this technique is the potential to reduce CO 2 emission owing to the use of clean energy (e.g., renewable electricity) that can transform the conventional fossil-fuel-powered thermal treatment into a more sustainable biorefinery process.…”
Section: Introductionmentioning
confidence: 99%
“…By valorizing the biomass byproducts such as HMF via clean energy, a circular economy model can be established, which benefits both the biorefinery industry and the general public, rendering the electrochemical oxidation of HMF a highly researched topic. A recent techno-economic analysis demonstrates the considerable merits of electrochemical oxidation of HMF in both energy and material perspectives compared with conventional thermal catalysis ( Patel et al., 2022 ). Another profound benefit of this technique is the potential to reduce CO 2 emission owing to the use of clean energy (e.g., renewable electricity) that can transform the conventional fossil-fuel-powered thermal treatment into a more sustainable biorefinery process.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the conventional thermochemical process, the renewable electricity pathway has lower-energy intensity and a milder environmental impact. Accordingly, Patel et al (2022) concluded that the processes of HMF production is the most significant factor in overall environmental impact in many categories. A similar study focusing on microalgae biomass, the most promising feedstock for third-generation biofuel production, demonstrated its great potential for bioethanol production, with a favorable net energy ratio (0.45) and net energy balance (–2,749.6 GJ y –1 ), as well as low water and land footprints in bioethanol production plants ( Hossain et al, 2019 ).…”
Section: Current Strategies For Assessing the Feasibility Of A Lignoc...mentioning
confidence: 99%
“…Consequently, the potential of the anode where the electrooxidation is happening must be as small as possible for a given cathode material. As shown in Figure 10b, HMF electrooxidation is less energy-demanding than OER [12], and its electrocatalysis can be regulated to produce value-added chemicals to replace petroleum-based polymers [10,12,13]. The linear sweep voltammetry (LSV) of Figure 10b shows that the presence of 50 mM HMF in 1 M KOH is accompanied by a drastic shift in the potential needed to drive more current density (and thus more conversion of the reactants into products, the second law of Faraday).…”
Section: Hmf Electrooxidation For Paired Electrosynthesis Of Valuable...mentioning
confidence: 99%
“…For instance, several candidates such as 2,5-diformylfuran (DFF), 5-hydroxymethyl-2-furancarboxylic acid (HFCA), 5-formyl-2-furancarboxylic acid (FFCA), and 2,5-furandicarboxylic acid (FDCA) have been generated by the oxidation of 5-hydroxymethylfurfural (HMF) under different conditions [2,[7][8][9]. HMF derives from cellulose and hemicellulose, the two primary constituents of lignocellulosic biomass (60-75%), and has the potential to be converted into platform biofuels [10,11]. Specifically, the biosourced compound HMF is an intermediate for the synthesis of bio-renewable FDCA, which is the monomer for the polyethylene furanoate (PEF) biopolymer materials of industrial relevance as it is a green alternative to polyethylene terephthalate (PET) [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation